From imitation to imutation: Conditions and consequences - Maksimov, V.; Sun, J.; Luo, Yadong; Ng, S. (2014)
We examine a neglected spectrum of activities, where imitation and innovation blend together. We refer to these firm activities as imutation, a mixture of imitation and mutation (transformation). The main purpose is to define and distinguish imutation from imitation and offer a framework revealing key conditions and outcomes of imutation.